Pengaruh Indeks Pembangunan Manusia, Pengangguran Dan Tenaga Kerja Terhadap Kemiskinan Di Kabupaten Halmahera Selatan - Injilia Guguraty; Tri Oldy Rotinsulu; Wensy F.I Rompas (Jurnal Riset Multidisiplin Edukasi, 2025)
Poverty is one of the crucial issues faced by various countries including Indonesia. As a developing country, poverty is not a new problem. Almost all government periods in Indonesia have placed poverty as a development issue, especially South Halmahera Regency as one of the areas in North Maluku Province. Poverty in this area fluctuates every year. This study aims to analyze the effect of the Human Development Index (HDI), Unemployment, and Labor on poverty in South Halmahera Regency. This study is a quantitative study, the type of data used is secondary data in the form of time series data from 2010 - 2023 sourced from the Central Statistics Agency. The data collected was processed using the multiple linear regression analysis method with the help of Eviews version 12. The results of the study show that: (1) HDI partially has a negative and significant effect on poverty in South Halmahera Regency. (2) Unemployment partially has a negative and significant effect on poverty in South Halmahera Regency. (3) The workforce partially has a positive and significant influence on poverty in South Halmahera Regency. (4) The Human Development Index, Unemployment (HDI), and the workforce simultaneously influence poverty in South Halmahera Regency.